Pengembangan Lembar Kerja Siswa (LKS) dan Media Penunjang Untuk Mengaktifkan Keterampilan Berpikir Kritis - Kuzaimah, Siti; Wati, Mustika; Hartini, Sri (Universitas Lambung Mangkurat, 2014)
Curriculum 2013 aims to encourage students to think critically in the learning process, but the results of UNDP (United Nations Development Programme) in 2010 showed critical thinking skills in Indonesia is still low. This research aims to produce worksheets and supporting media that can stimulate students critical thinking skills. This type of research is the development of models ASSURE (Analyze Learners, State Objectives, Select methods, media, and materials, Utilize Material, Requires Participation Learners, Evaluate and revise). Test subjects were students of grade IX SMP Negeri 1 Aluh-Aluh. Implementation research is to develop the initial design and media supporting worksheets, reviewed by experts (faculty) and practitioners (junior high science teacher) and tested in grade IX students of SMP Negeri 1 Aluh-Aluh. Data obtained from the test results, observations, questionnaires, and documentations. Data analyzed in descriptive and qualitative. Analysis results of students critical thinking skills after using worksheets and supporting media, there is a very good category 12.5% of students, 59.4% good students, good enough 25% of students, and 3% poor students. Students response to LKS categorized 78.9% good, and the students response to the media at 82.9% well categorized. As conclution the developed worksheet and the media support material of the solar system is able effective to stimulate critical thinking skills of junior high school students.Â